PENERAPAN METODE BRAINSTORMING MEDIA GAMBAR TERHADAP HASIL BELAJAR SISWA PELAJARAN SEJARAH MA MATHLA’UL ANWAR PONTIANAK - Habib Al - ham; Sulistyarini Sulistyarini; Ika Rahmat (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis study aims to determine the effect of the application of Image Media Assisted Brainstorming Method to the learning outcomes of students of class X IIS 3 Madrasah Aliyah Mathla'ul Anwar Pontianak. This study used the Quasi Experimental method with the design of "Nonequevalent Control Group". The population in this study were all students of class X IIS Madrasah Aliyah Mathla'ul Anwar Pontianak and the sample of this study were students of class X IIS 3 Madrasah Aliyah Mathla'ul Anwar Pontianak,which amount to 21 people. Data collection instruments in this study used interview sheets, observation sheets, and test sheets in the form of item writing, validity and reliability. The results of data analysis obtain the average value of 50 control class pre-test, 51.5 experimental class and the control class average post-test score of 65 and experimental class 79.25. Based on the results of the calculation of the Hypothesis Test (Test - t) it is known the value of tcount (6.68)> ttable (2.02) then Ha is accepted and Ho is rejected. This means that there is a significant effect of the application of Image Media Assisted Brainstroming Method on the learning outcomes of class X IIS 3 students. So, conclution for the application of the Image Media Assisted Brainstorming method was successfully applied in improving the history of student learning outcomes in class X IIS 3 Madrasah Aliyah Mathla'ul Anwar Pontianak.Keywords: Brainstorming Method, Image Media, Learning Outcomes